Lexical Density Across Languages: A Contrastive Analysis of English and Indonesian Academic Prose - Raudhotul Fadhilah; Irpi Octia Pebrianti; Alya Fadhillah Dalimunthe; Cindy Alia Ramadhany; Siti Ismahani (Jurnal Ilmiah Multidisiplin, 2026)
This study investigates lexical density in English and Indonesian academic prose using a qualitative contrastive approach. Drawing on authentic journal articles from comparable academic fields, the analysis focuses on how each language organizes and packages meaning in academic writing. The findings reveal that English academic prose tends to achieve high lexical density through nominalization and complex noun phrases, allowing writers to compress information and advance arguments in an abstract and cumulative manner. Indonesian academic prose, by contrast, often develops meaning through verbal clauses and explicit relational markers, resulting in a more elaborative and linear style. These differences reflect distinct discourse preferences rather than differences in academic quality. The study explains how such contrasts contribute to difficulties experienced by Indonesian writers when producing English academic texts. It also highlights the importance of contrastive awareness in academic writing instruction and evaluation